Poland: National Regulations in the Shadow of the Common Past – Criminal Law - Wielec, Marcin (Criminal Legal Studies: European Challenges and Central European Responses in the Criminal Science of the 21st Century, 2022)
Criminal law regulations in each country are among the most delicate and most important legal acts for the functioning of the society. Criminal liability determined in the course of criminal proceedings is the most controversial type of legal liability because unlike other types, it allows, in the majesty of the law, for the deepest type of interference with the status of a free individual, specifically, the status of their rights. Additionally, the positive result of criminal proceedings, namely the statement that someone did indeed commit a crime, has very serious consequences. This is because in general, criminal law is public law, wherein this interference with individuals’ rights and freedoms is most apparent. Therefore, on the one hand, in the area of criminal law, there must be a specific balance between the necessity to interfere with the rights of an individual by a public authority and the securing of these rights against possible abuses of this authority. On the other hand, the area of criminal law is particularly susceptible to a wide variety of historical events as well as political, social, and economic influences. This primarily regards time in the sense of historical events, the specificity of the period, or simply the attitude of public authorities toward an individual in society. In this line of thought, analyses showing the general characteristics of each criminal law system, in this case, the system functioning in Poland, are recent and highly interesting.KEYWORDS: Poland, penal system, criminal law, criminal proceedings, the evolution of criminal law in Poland